ALS Multicenter Cohort Study of Oxidative Stress (ALS COSMOS): Study methodology, recruitment, and baseline demographic and disease characteristics. Issue 3 (1st June 2014) - Mitsumoto, Hiroshi; Factor-Litvak, Pam; Andrews, Howard; Goetz, Raymond R.; Andrews, Leslie; Rabkin, Judith G.; McElhiney, Martin; Nieves, Jeri; Santella, Regina M.; Murphy, Jennifer; Hupf, Jonathan; Singleton, Jess; et al.
Abstract: In a multicenter study of newly diagnosed ALS patients without a reported family history of ALS, we are prospectively investigating whether markers of oxidative stress (OS) are associated with disease progression. Methods utilize an extensive structured telephone interview ascertaining environmental, lifestyle, dietary and psychological risk factors associated with OS. Detailed assessments were performed at baseline and at 3–6 month intervals during the ensuing 30 months. Our biorepository includes DNA, plasma, urine, and skin. Three hundred and fifty-five patients were recruited. Subjects were enrolled over a 36-month period at 16 sites. To meet the target number of subjects, the recruitment period was prolonged and additional sites were included. Results showed that demographic and disease characteristics were similar between 477 eligible/non-enrolled and enrolled patients, the only difference being type of health insurance among enrolled patients. Sites were divided into three groups by the number of enrolled subjects. Comparing these three groups, the Columbia site had fewer 'definite ALS' diagnoses. This is the first prospective, interdisciplinary, in-depth, multicenter epidemiological investigation of OS related to ALS progression and has been accomplished by an aggressive recruitment process. The baseline demographic and disease features of the study sample are now fully characterized.